Pendataan Masyarakat sebagai Fondasi Perencanaan SDGs di Desa Sidodadi, Kecamatan Ngantang, Kabupaten Malang - Taroreh, Dika Aurelya Aleandra; Dina Shofiana; Karina Aurel Naviezenia; Bagas Dwi Ardianto; Muhammad Zainur Rifqi; Meyshela Gracia; Wildan Kanzul Fitri; Enanto Harun Satrio; Reihan Fitroh Aldisar9; Abdul Rahman Prasetyo (Innovative Journal of Community Engagement, 2025)
The community survey in RT 12, Sidodadi Village, Ngantang District, Malang Regency, was carried out to obtain a comprehensive overview of the social, economic, and demographic conditions as a foundation for planning village development programs in line with the Sustainable Development Goals (SDGs). Using a quantitative method through door-to-door interviews, a total of 47 households participated in the survey, which collected data related to employment, health status, education level, household conditions, and social assistance received. The findings show that the majority of respondents work in the agricultural sector and dairy cattle farming, with some households recorded as recipients of social assistance, and relatively low levels of education, which indicates an urgent need to improve access to education and skills training. Although there were challenges such as respondents’ limited time and their lack of understanding of the survey’s purpose, the collected data is sufficiently representative to support more effective planning of the Village SDGs program. Thus, focusing on the agricultural and dairy farming sectors, improving access to education, and encouraging active community participation are essential to enhance the quality of life in Sidodadi Village.